Аналіз і класифікація методів штучного інтелекту при застосуванні до задач оптимізації в мережах 6G - Скомаха, М. О.; Єременко, О. С. (ХНУРЕ, 2023)
This work reviews and analyzes methods and technical solutions in network optimization and its performance in 6G based on artificial intelligence. Without optimization measures in mobile networks, providing high-quality services to customers and maintaining demanded performance is impossible, so it was decided to introduce AI and machine learning methods for the next-generation mobile networks. This will allow for more efficient resource allocation and segmentation of elements without additional administration efforts, which will be mentioned and discussed in this work.
Keywords: оптимізація в мережах 6G; штучний інтелект